RETRACTED: Artificial intelligence: Enhancing monitoring and assessment of natural ecosystems, businesses and engineering - Guzueva Elina; Abdulmukminova Fatima; Kremleva Elmira (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001